Comparison of Microhardness of Three Different Types of Acrylic Artificial Denture Teeth: An in vitro Study - Khanna, Gagan; Aparna, IN (Journal of Orofacial Research, 2013)
The wear resistance of denture teeth is important for the longevity of removable prostheses of edentulous patients. The ability of denture teeth to maintain maximum intercuspation at centric jaw relation position, masticatory efficiency, the occlusal vertical dimension, and occlusal stability over time may be influenced by this property. Inferior wear resistance of acrylic resin artificial teeth is a significant limitation for complete denture therapy due to its inability to resist parafunctional movements and maintain proper occlusal relationships over time. Therefore acrylic resin teeth have been modified to overcome these disadvantages by the use of cross-linking agents, different monomers, and the addition of fillers. In the present study microhardness is compared of the different acrylic teeth since it is related to wear resistance and is the most commonly examined mechanical property indicator for synthetic artificial tooth material.